PENISTAAN/PENODAAN AGAMA DALAM PERSPEKTIF PEMUKA AGAMA ISLAM DI PROVINSI NUSA TENGGARA BARAT (NTB) (Harmoni, 2016)
Historically, the exsistence of UU N0. 1/ PNPS/1965 was made to protect the Nation and Society,where misleading or religious humiliation are viewed as a revolutional tread. By the rise of certain orders/sects, which was assumed against the religious teachings and laws then it is essentially needed to have national awareness by bringing out this regulations. On the other hand supporting the exsistence of the Regulation or UU No. 1/ PNPS/1965 was considered as a form of freedom in expressing their faith, meanwhile on the other side is considering to triggering conflict because it is against the mainstream of religious understanding.This condition has become the main factor to create chaos in religious life.  The religious leaders and the Islamic organization leaders in Mataramshows that there are same tendencies in viewing the Regulation or UU No.1/PNPS/1965. Most of religious leaders and the Islamic organization leaders said that they knew the Regulation or UU No.1/PNPS/1965, while some of them said that they have not know it, even reading it, yet. Among the religious leader said that there weresome case of religious desacration among others, for example: the case ofCongregation of Ahmadiyah, A thariqah (spiritual path) that teaches Inner Marriage (Nikah Batin) who can be married more than 4 wives in Lombok Tengah, Namatan Prayer, andΓÇ£Amak BakrieΓÇ¥who confess his self as the prophet.  The objective of this research is to comprehend knowledge and understanding of the religious leaders and the Islamic organization leaders in understanding the content of Regulation/UU No. 1/PNPS/Year 1965. The conclusion of this research related about the knowledge and understanding the content of the Regulation orUU No. 1/PNPS/Year 1965 is understandable by religious leaders. According to them, religious desecration is against the main teachings of religion. Due to the benefit of that particular regulation they consider that this Regulationmust be aprehend. Meanwhile, related to the punishment for the man who practising religious desecration is 5 years maximum in prison especially for the initiator for the sake of deterrent effect.
Keywords: UU PNPS; Islamic Leaders; Religious Defamation; kasus penistaan/penodaan dan sangsi hukuman; UU No. 1/PNPS/1965; arus utama; kurang kondusif; Kebebasan beragama